Development of Android Applications Based on Discovery Learning for Interactive Learning Media for Islamic Religious Education - Rifai, Ikhsan; Nurhaliza, Nurhaliza (International Journal of Education, Information Technology, and Others, 2024)
The use of Android smartphones is predominant in schools, including in Islamic Education (PAI) subjects. Studies show that smartphones are frequently used in learning, but they also contribute to gaming addiction among students. Banning smartphone use is not always effective; however, if utilized properly, they can offer significant benefits. Criticism of PAI in schools includes an overemphasis on memorization, particularly in history lessons. Research at SMA Negeri 1 Kalasan indicates that students are allowed to use smartphones in class, highlighting the need for a more directed approach to technology use. This study employs a Research and Development (R&D) model, specifically the 4D model, which consists of define, design, develop, and disseminate stages. Data was collected through questionnaires and validation sheets. The learning media was validated in two stages, assessing instructional, media, and content aspects. The learning media was trialed in both small and large groups to gauge student responses. The subjects of the study were students in class X-1 Phase E at SMA Negeri 1 Kalasan. The instruments used were developed and validated by experts in Educational Technology. Data analysis techniques involved calculating averages and converting them into percentages. The research findings indicate: 1) Initial analysis identified significant needs from PAI teachers and students for Android-based learning media. The learning media focused on the Walisongo material for class X, with the final product in .apk file format. 2) First-stage assessments by instructional, media, and content experts showed validity scores of 76.67% (valid), 80.00% (valid), and 73.33% (valid), respectively. In the second-stage assessments, validity scores improved to 91.67% (very valid), 98.00% (very valid), and 86.67% (very valid). 3) Student responses from both small and large group trials indicated a validity level of 87.2% (very valid) and 90.0% (very valid). The learning media is deemed suitable and practical for use and has been disseminated through the application store, registered with a Copyright Registration Certificat.